Diskursus Limitasi Hak Imunitas Ahli dalam Konstruksi Hukum Nasional - Arman Tjoneng; Dian Narwastuty; Keysha Azkia Salsabila (Faculty of Law, Maranatha Christian University, 2022)
Expert testimony in criminal evidence is needed to explain a case clearly so that the judge can decide a legal case with full objectivity. In fact, experts who provide their statements are often used as defendants because their statements are considered detrimental to the defendant's position so that the defendant sues the expert to court. The approach method used is a normative legal research method, namely legal research conducted by examining library materials or secondary data. The approach used is a statutory approach, a case approach and a conceptual approach. Experts have immunity in providing their statements based on professionalism and good faith, so that the Expert cannot be prosecuted either criminally or civilly. If forced, there will be a weakening of the independence of the Experts and will disrupt the existing judicial system. However, if the Expert in providing his statement is not based on good faith and manipulates the data so that it benefits a certain party, then the Expert can be prosecuted through the PMH channel. In order to strengthen the immunity of the Expert, there must be a strict rule stating the protection of the expert who has good intentions.